PENGARUH KUALITAS PELAYANAN, HARGA, DESAIN PRODUK, DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN MAHASISWA PADA APLIKASI SHOPEE (STUDI KASUS MAHASISWA JURUSAN FARMASI UNIVERSITAS PERINTIS INDONESIA) - Syaiful Anwar; Mhd Aldiansyah Lubis (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2021)
The growing internet today encourages companies to determine the right marketing strategy to survive and win the competition from its competitors. Like using the Shopee application as an e-commerce or online trade used in marketing products and services. The population in this study were students of the Department of Pharmacy, Universitas Perintis Indonesia TA. 2017-2020 as many as 659 students. The research sample was 87 students with sampling technique using non-probability sampling technique with purposive sampling technique or sampling technique with certain considerations. Data collection was carried out by distributing questionnaires while data processing used validity tests, reliability tests, multiple linear regression analysis and t tests using SPSS version 20. The results of this test prove that service quality, price, product design and celebrity endorsers have a positive and significant influence. to purchasing decisions.